Sociodemographic and Health-related Determinants of COVID-19 Prevalence and Case Fatality Rate in Indonesia - Izzy Suraya; Mochamad Iqbal Nurmansyah; Nia Musniati; Elia Nur Ayunin; Catur Rosidati; Ibrahim Isa Koire (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
Indonesia is a country with the highest COVID-19 confirmed cases and mortality rate among southeast Asian countries. This study was conducted to identify the correlation between sociodemographic factors and the number of confirmed cases and mortality rates due to COVID-19 in Indonesia. This research is an ecological study where secondary data published by the Indonesian government was used. Spearman correlation were used in this study. This study showed that sociodemographic conditions in Indonesia varied greatly. Spearman correlation test results showed that a significant relationship (p-value < 0.05) between the number of COVID-19 confirmation cases with population density, population growth, decreased mobility outside the home, hypertension and diabetes prevalence, number of health workers (general practitioners, specialist doctors, and nurses) as well as the number of COVID-19 specialized hospitals. Significant correlations (p-value < 0.05) were also shown by the relationship between COVID-19 mortality rates and a dense population, a large decrease in mobility to the workplace, number of smokers, and number of health workers. Equitable development is expected to reduce sociodemographic and health disparities so that each region has good preparedness in dealing with outbreaks without the occurrence of areas that are more severely affected by outbreaks compared to other regions.